Petrografia, geoquímica e geocronologia Sm/Nd das rochas do complexo máfico - ultramáficos trincheira : divisa Mato Grosso-Rondônia, Sw do Cráton Amazônico - Oliveira, Regiane Ferreira de (2014)
This works presents the results of Geological studies and petrographics realized in the Noroagro District, Comodoro municipality of Mato Grosso State focused on Geochemistry and Sm/Nd geochronology of dykes and maphic plugs emplaced in Rio Piolho Granite and Rio Galera Complex. The studied dykes is located in southwest of Amazonian Craton, Rondonian-San Ignácio Province, specifically in the Alto Guaporé Belt. Petrographically the rocks exhibit macroscopic strutural feature characteristics of massiveslightelly oriented rocks, fine to médium grain ranging of mafic to utramafic composition and greenhish – gray to black color. They presets inequigranular textures and gabbroic or peridotite composition, consisting essentially of mafic minerals (pyroxene and amphibole) and sometimes altered plagioclase and its partial saussuritization process. Optically Show holocrystalline granular rocks, with cumulate and ophitic texture ( peridotites) where pyroxene representes the cumulus crystal phase and the plagioclase inter-cumulus phase. Geochemical data emphasize that the magmatism is tholeiitic with sub-alkaline nature, being all of the rocks in the field of Ocean Floor Basalts (OFB) and two samples representes signatures island arc. Geochoronological Sm-Nd data indicated ages of 1,24 ,1,27 and 1,57 (Ga) and Show ɛ Nd (t)a between + 6,27 and +6,50 for gabbro and +5,80 for pyroxenite. The positive ɛ Nd (t)a values together with razão 87Sr/86Sr ratio of 0,704 for metagabbro suggests for the mafic- ultramafic rocks of region of Maringa and Imaculada Farm are derived of depleted mantle.